(3GdbOQGJ GdbjGOjI GdCQHYs (3bjGOI GdCaQGO ef NdGd GdWHjYIs - (3gfOQjT, aQjJTs; (3fUQj, SGeQs ((3GdQjGVs (3ecJHI GdYHjcGfs, 2006)
(3jYed PG GdcJGH aj GdhGbY Ydj QHW GdLShQ GdVQhQjI GddGReI ajeG Hjf GdGOGQI h GdbjGOIs
(3GdfU eJQLe Edi GddZI GdYQHjI ef GddZI GdCdeGfjIs
1 10 11 12 13 20
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQIs; (3GdbjGOI GdEOGQjIs; (3GdbjGOIs